2014
DOI: 10.12693/aphyspola.125.1010
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Analysis of Oxygen Precipitation around Small-Angle Grain Boundaries in Multicrystalline Silicon Wafers

Abstract: We have investigated the correlation between deep-level photoluminescence and the density of small-angle grain boundaries in multicrystalline Si. A deep-level photoluminescence component around 0.87 eV, which we previously ascribed to oxygen precipitates, became lower and higher in the region with high and low density of small-angle grain boundaries, respectively. This can be explained by the dierences in the availability of oxygen atoms around respective small-angle grain boundaries. We performed focused ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They can also be introduced in device fabrication processes, even in monocrystalline CZ‐Si, from precipitates (Tachibana et al ., ), GBs (Kutsukake et al ., ) and stacking faults (Kivambe et al ., ). They are preferentially segregated with oxygen atoms (Kato et al ., ), depending on the tilt angle (Tajima et al ., ), and they deteriorate solar cell efficiencies via the segregation (Tachibana et al ., ). Meanwhile, the GBs with tilt angle larger than about 10°, so‐called large‐angle tilt boundaries (LATBs), can be characterized with Σ values within the coincidence site lattice model.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be introduced in device fabrication processes, even in monocrystalline CZ‐Si, from precipitates (Tachibana et al ., ), GBs (Kutsukake et al ., ) and stacking faults (Kivambe et al ., ). They are preferentially segregated with oxygen atoms (Kato et al ., ), depending on the tilt angle (Tajima et al ., ), and they deteriorate solar cell efficiencies via the segregation (Tachibana et al ., ). Meanwhile, the GBs with tilt angle larger than about 10°, so‐called large‐angle tilt boundaries (LATBs), can be characterized with Σ values within the coincidence site lattice model.…”
Section: Introductionmentioning
confidence: 99%
“…As oxygen continues to diffuse from crucibles or other sources into the Si material at high temperature, it is likely that the small-angle boundaries resulting from unresolved thermal stresses in the interiors of large grains have not been decorated by other impurities; thus, they are prime locations for oxygen precipitates to form. Recent work has shown that oxygen precipitates at small-angle grain boundaries are more prevalent in slowly solidified samples than in silicon that undergoes a faster solidification based on deep-level photoluminescence (PL) and time-of-flight secondary ion spectrometry (TOF-SIMS) analysis (Katoa et al, 2014). Other PL studies have also suggested that small-angle grain boundaries may be more likely sites for oxygen precipitates to form in mc-Si due to the presence of unresolved strain surrounding these types of boundaries (Tajima et al, 2012).…”
Section: Impurity Precipitates and Small-angle Grain Boundariesmentioning
confidence: 99%